Case report: Accelerated regression of giant cardiac rhabdomyomas in neonates with low dose everolimus - Hurtado-Sierra, Daniel; Ramos Garzón, Judy Ximena; Rojas, Lyda Z.; Fernández-Gómez, Oscar; Manrique-Rincón, Francisco (Frontiers in Pediatrics, 2023)
Cardiac rhabdomyoma (CRHM) is the principal cardiac tumor in children and is most often associated with tuberous sclerosis complex (TSC). Mutations in the TSC1 and TSC2 genes cause the overactivation of the mammalian Target of Rapamycin (mTOR). This protein family is responsible for abnormal cell proliferation leading to the formation of CRHMs and hamartomas in other organs. Despite the tendency for spontaneous regression, some CRHMs can cause heart failure and intractable arrhythmias, requiring surgical resection. In recent years, the use of everolimus and sirolimus (mTOR inhibitors) in the treatment of CRHMs has been reported. We report two cases of neonates with giant rhabdomyomas, with hemodynamic repercussions treated with low-dose everolimus (4.5 mg/m2/week). In both cases, we obtained an approximate decrease of 50% in the total area of the mass after three weeks of treatment. Despite rebound growth after stopping the drug, we were able to evidence that the use of low doses of everolimus immediately after birth is effective and safe in the treatment of giant CRHMs, avoiding surgical resection of the tumor and associated morbidity and mortality.